(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2014)
A study was conducted on the enrichment of manganese oxide tailings material generated from sorting spiral concentration at Ghana Manganese Company (GMC) Limited, Nsuta. The investigation explored mineralogical and particle size characterisation and heavy medium separation technique. Analytical methods used include; X-Ray Fluorescence and Atomic Absorption Spectrometry (AAS). The material contained 9.01% Al2O3, 27.43 % SiO2, 23.64% MnO2 and 9.86% Fe2O3, the other oxides range between 0.04 to 1.55 %. By treating the individual size fractions at a bath density of 2.96, the highest ratio of concentration of 3.56 was obtained at 180 ?m, while the highest enrichment ratio of 1.84 and manganese grade of 38.25% were obtained at 1180?m respectively. These qualify the enriched material as suitable for Ferro-alloy industry. DOI: http://dx.doi.org/10.3329/bjsir.v49i1.18852 Bangladesh J. Sci. Ind. Res. 49(1), 35-40, 2014